Synthesis and characterization of novel guanidine ligands featuring biphenyl or binaphthyl backbones - Maronna, Astrid Christine; Bindewald, Elvira; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
In this paper we report on the synthesis and characterization of several new 2,2′-bisguanidino-1,1′-biphenyl and -binaphthyl ligands as well as the electron donor 3,3′,4,4′-tetrakis(tetramethylguanidino)-1,1′-biphenyl. Chiral bisguanidine ligands were prepared with binaphthyl backbones. The solid-state structures were analysed by single-crystal X-ray diffraction. UV/Vis and Raman spectra provided a qualitative insight into the rotational barriers in solution and in the solid state. Finally, late-transition-metal complexes of two of these ligands were prepared. These complexes prefer a κ1 rather than a κ2 coordination mode. The discussion of the experimental results is complemented by quantum chemical (DFT) calculations. Finally, we report on the first catalytic test reactions.